Material characterization of different-dimensioned wood particle-reinforced polymer composites - Akdogan, Anil; Vanli, Ali Serdar (SAGE PUBLICATIONS LTD, 2013)
Different national resources like nut shells and residual wood flours (WFs) are being used as filler materials of polymer composites. It is possible to obtain proper composites from high percentage addition of different sized wood chips to the polymer raw material. This article investigates the effects of three different-dimensioned beech flours as additives on the morphological and mechanical properties of the polymer composite materials. At lower particle sizes, loading of certain concentrations of WF results in better mechanical properties and morphological improvements in composites are experienced.
Keywords: Polymer composites; wood additives; particle size; mechanical properties; morphology; MECHANICAL-PROPERTIES; EXTRUSION; FLOUR; SIZE; Materials Science